FAKTOR VARIABEL PENYEBAB TURUNNYA GROWTH ECONOMIC KAWASAN FTZ DI KEPULAUAN RIAU - Syarif Hidayah Lubis (Jurnal Dinamika Ekonomi & Bisnis, 2019)
Of the 4 regions of the Free Trade Zone (FTZ) in Indonesia, Riau Islands has 3 regions, namely Batam, Bintan and Karimun, however, in the last 5 years the FTZ area has experienced less optimal economic growth or is experiencing a decline. Overall economic growth in the Riau Islands FTZ region During the last 6 years there has been a cumulative 6-year decline, namely Batam city at -0.476, Bintan -0.18 Karimun regency at -0.172. There are several drivers of economic growth in the FTZ region including tourism, MSMEs and inflation. The purpose of this study was to find out the variables that influence the decline in the Economic Growth / GRDP of the FTZ region in the Riau Islands Province. This study uses quantitative research by obtaining secondary data and the techniques used in collecting data are by documentation techniques, namely recording and copying of secondary data. The simultaneous results of the variables of Tourism, MSME and inflation have an effect on the Economic Growth / GRDP, simultaneously the variables of Tourism, MSMEs and inflation have an effect on Economic Growth / GRDP. Partially the tourism / tourist variables have a negative influence on economic growth / GDP. This can be seen tcount (-3.503) <ttable (1.67356) significant value (0.001) <(0.05), MSME variables have a positive effect on Economic Growth / GRDP with tcount (2.841)> t table (1.67356) and significant value (0.016) <(0.05). PMA has no effect on Economic Growth / GRDP. This can be seen with the value of tcount (1.535) <ttable (1.67356)) and significant value (0.131)> (0.05), Exports have an effect on Economic Growth / GRDP with tcount (1.803)> ttable (1.67356) and significant value (0.047) <(0.05), Inflation has an effect on Economic Growth / GRDP with tcount (0.439) <t table (1.67356) and significant value (0.662)> (0.05).